The Effectiveness of the E-Book “Aku Siap Pubertas (ASiaP) in Enhancing theRole of Parents and Children's Readiness for Puberty - Mardeyanti, Mardeyanti; Karningsih, Karningsih; Yulfitria, Fauziah; Darwanty, Jundra (jitek, 2023)
Adolescents experience successive hormonal, physical, psychological and social changes. Adolescents detach themselves emotionally from their parents to assume social roles. As many as 47.7% of teenagers often feel anxious, and 84% feel repeated feelings of anxiety. One of the anxieties that are handled is the physical changes during puberty. The results of this research on family support are still relatively low, namely 12%. Families are overprotective, lack attention, and feel confused about adolescent emotions. Objective: To determine the effect of e-books on knowledge, attitudes, mother's role and children's readiness to face puberty. Methods: The research design is quasi-experimental. They conducted research in March-September 2022 in the Malaka Jaya sub-district, East Jakarta, with a total sample of 59 mothers and adolescents. The data results were analyzed using the non-parametric Wilcoxon Rank and linear regression tests. Results: This study shows the effect of e-books on knowledge, attitudes and the role of mothers in dealing with pubertal changes with a significance of 0.000, 0.04 and 0.000. Education affects learning with a value of 0.000 and a regression coefficient of 2.787, which means that education increases a mother's knowledge by 2.7 times. There 91.1% of children are ready to be cheerful and ready to go through puberty, with a significance of 0.002. Conclusion: Using e-books increases mothers' role in facing puberty changes, and adolescents can go through puberty well.